Search for Efficiency in the Adjustment Process : Spain in the 1980's; Op 57. (Occasional Papers; Occasional Paper ;, 1988)
This paper discusses the main features of Spain's recent adjustment effort and assesses its impact on the overall economic situation. It provides a brief historical background on Spain's economic development from 1960 to the early 1980s. The chapter also discusses the authorities' stance on monetary and fiscal policy and examines the role of exchange rate policy in the recovery of the external accounts. The progress in the fiscal area would appear to have been less satisfactory when viewed in terms of the size of the nonfinancial deficit, which over 1982-1986 hovered about 5.5 percent of gross domestic product. The government's medium-term economic strategy is to consolidate the recent gains by maintaining the economy on a path of noninflation growth. Monetary policy is likely to continue to play an active role in this process, as was made clear in early 1987 when the Bank of Spain tightened its stance significantly in response to the buoyancy of domestic demand and the concomitant expansion of private sector credit.